Linking turnover to organizational performance: the role of process conformance. Issue 5 (4th May 2019) - Wynen, Jan; Van Dooren, Wouter; Mattijs, Jan; Deschamps, Carl
ABSTRACT: Despite substantial evidence for the negative effect of turnover on performance, several studies also note offsetting positive effects hereby recognizing an optimal rate of turnover. These mixed results stress the need to examine under which conditions turnover is more harmful or beneficial to the organization. Using panel data from 30 divisions of the same agency, this study examines the impact of process conformance – the extent to which there are prescribed standards and rules related to the task. Results support a non-linear, inverted U-shaped relationship for those tasks with a high process conformance.